2014
DOI: 10.1128/jcm.00688-14
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing Scheme versus Pulsed-Field Gel Electrophoresis for Typing Mycobacterium abscessus Isolates

Abstract: hOutbreaks of infections by rapidly growing mycobacteria following invasive procedures, such as ophthalmological, laparoscopic, arthroscopic, plastic, and cardiac surgeries, mesotherapy, and vaccination, have been detected in Brazil since 1998. Members of the Mycobacterium chelonae-Mycobacterium abscessus group have caused most of these outbreaks. As part of an epidemiological investigation, the isolates were typed by pulsed-field gel electrophoresis (PFGE). In this project, we performed a large-scale comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…These results confirmed the elevated discriminatory power of this method for diversity studies of these species, as shown in previous studies (33,34).…”
Section: Discussionsupporting
confidence: 77%
“…These results confirmed the elevated discriminatory power of this method for diversity studies of these species, as shown in previous studies (33,34).…”
Section: Discussionsupporting
confidence: 77%
“…Clonal relatedness was established on the basis of MLST analysis. Although pulsed field gel electrophoresis (PFGE) has historically been used to define outbreaks and clusters (Dizbay et al, 2009;De Smet et al, 2013), the technique is cumbersome, requiring dedicated equipment that is not widely available (Machado et al, 2014). Many recent studies have explored the potential of MLST as a tool for detailed investigation of outbreaks (Mali et al, 2017;Singhal et al, 2015;Wang et al, 2015;Sails et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have explored the potential of MLST as a tool for detailed investigation of outbreaks (Mali et al, 2017;Singhal et al, 2015;Wang et al, 2015;Sails et al, 2003). Also, studies comparing the results of MLST schemes to PFGE have shown 100% agreement between the two techniques (Machado et al, 2014). MLST is also the method of choice for typing BCC due to its ability to differentiate the species in BCC complex (Mahenthiralingam et al, 2008;Vandamme and Dawyndt, 2011;Gautam et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…MLST analyses targeting seven housekeeping genes were applied to investigate the genetic diversity of the two putative recombinant strains. The seven target genes were argH (argininosuccinate lyase), cya (adenylate cyclase), glpK (glycerol kinase), gnd (6-phosphogluconate dehydrogenase), murC (UDP N-acetylmuramate-L-alanine ligase), pta (phosphate acetyltransferase) and purH (phosphoribosylaminoimidazole carboxylase ATPase subunit) [28, 29]. Also, erm (41)-targeted PCR was applied to the reference strain and to two Rec-mas-H strains [30, 31].…”
Section: Methodsmentioning
confidence: 99%